PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS IV SD NEGERI 79 PEKANBARU - Eddy Noviana; Muhammad Nailul Huda (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This study aims to improve PKn learning outcomes of fourth grade students of SD Negeri 79 Pekanbaru with the application of STAD type cooperative learning model. This research is a classroom action research conducted in SD Negeri 79 Pekanbaru, the subject of this research is the fourth grade students with a total of 40 students. The results showed that the students' learning outcomes on the baseline score an average score of 48.61 increased by 16.95 points to 65.56 in cycle I. In the second cycle the average value of 71.67 increased from the first cycle of 6.11 points. Classical completeness in the basic score of 33% (18 students). In the cycle I test, the completeness increased to 72.5% (27 students). In cycle II, classical completeness completes to 87.5% (35 students). From the results of the study, it can be concluded that the application of cooperative learning model student team achievement division (STAD) can improve the learning outcomes of Civics students in grade IV SD Negeri 79 Pekanbaru.